Pendampingan Strategi Promosi dan Diversifikasi Produk Ubi Kremes pada UMKM Rumahan Snack Kelurahan Dalung Cipocok Jaya: Pengabdian - Azizah, Oktafia; Wahyu Wiguna; Sukma Pratama; Irwanto; Alifah; Jane (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
MEs are a key pillar of the national economy, playing a significant role in creating jobs and improving community welfare. However, many MSMEs face challenges in expanding their markets, particularly in promotion and product innovation. This community service activity aims to improve the competitiveness of the "Rumahan Snack" MSME in Dalung Cipocok Jaya Village through mentoring on promotional strategies and diversification of crispy sweet potato-based products. The implementation method includes initial observation to identify problems, training on digital media-based promotional strategies, and mentoring on the product diversification process into several attractive flavors and packaging variants. The results of the activity indicate an increase in MSME actors' understanding of modern marketing techniques, improved skills in managing social media as a promotional tool, and the emergence of new product variants with higher selling value. This activity is expected to encourage business sustainability and expand the market reach of the "Rumahan Snack" MSME in the future